Seaweed essential oils as a new source of bioactive compounds for cyanobacteria growth control: Innovative ecological biocontrol approach - Zerrifi, Soukaina El Amrani (2018)
This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). The application of natural compounds extracted from seaweeds is a promising eco-friendly alternative solution for harmful algae control in aquatic ecosystems. In the present study, the anti-cyanobacterial activity of three Moroccan marine macroalgae essential oils (EOs) was tested and evaluated on unicellular Microcystis aeruginosa cyanobacterium. Additionally, the possible anti-cyanobacterial response mechanisms were investigated by analyzing the antioxidant enzyme activities of M. aeruginosa cells. The results of EOs GC-MS analyses revealed a complex chemical composition, allowing the identification of 91 constituents. Palmitic acid, palmitoleic acid, and eicosapentaenoic acid were the most predominant compounds in Cystoseira tamariscifolia, Sargassum muticum, and Ulva lactuca EOs, respectively. The highest anti-cyanobacterial activity was recorded for Cystoseira tamariscifolia EO (ZI = 46.33 mm, MIC = 7.81 µg mL−1, and MBC = 15.62 µg mL−1). The growth, chlorophyll-a and protein content of the tested cyanobacteria were significantly reduced by C. tamariscifolia EO at both used concentrations (inhibition rate >67% during the 6 days test period in liquid media). Furthermore, oxidative stress caused by C. tamariscifolia EO on cyanobacterium cells showed an increase of the activities of superoxide dismutase (SOD) and catalase (CAT), and malondialdehyde (MDA) concentration was significantly elevated after 2 days of exposure. Overall, these experimental findings can open a promising new natural pathway based on the use of seaweed essential oils to the fight against potent toxic harmful cyanobacterial blooms (HCBs).